(untitled) (Konferensiyalar | Conferences, 2024)
A fictional text (belles-lettres text), being one of the forms of literary communication, has peculiar features which distinguish this text type from other types of communication. The problem of fictional texts has received widespread attention among linguists. The basic notions of fiction such as imagery, emotiveness, implicitness, ambiguity, associative potential, creativity, semantic complexity were discussed in the works by V.V. Vinogradov, B.A. Larin, G.O, Vinokur, R.O. Jackobson and others.